Compare the Efficacy of Ipratropium Bromide with Salbutamol and Salbutamol Alone in Recurrent Wheezes in Children with Asthma Presenting to LRH, Peshawar - Furqan Ahmad, Sohail Akhtar, Sana Nafis, Zulqarnain Haider, Mujtaba Gul, Ghulam Hussain, Fazal Badshah, Nizam Ud Din, Faiza (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Evaluate the effectiveness of Ipratropium Bromide in combination with Salbutamol and Salbutamol alone for the treatment of recurrent wheezes in children with asthma who seek care at LRH, Peshawar. Methods: After the approval from the institution review board, this randomized controlled trial was performed at Department of Pediatrics, LRH, Peshawar, from 7th January 2021 to 7th July 2021. A total of 128 patients who met the inclusion criteria were recruited from the Department of Pediatrics at LRH Peshawar. In Group A, 64 patients were given Ipratropium Bromide in addition to Salbutamol, whereas in Group B, 64 patients were given Salbutamol alone. In group A, children were subjected to salbutamol 2.5 mg thrice a day plus ipratropium bromide 125 ug 8 hourly during the exacerbation episode. In group B, children were subjected to 2.5 mg of salbutamol thrice a day during the exacerbation episode. Patients were contacted three months later to assess progress, and outcomes were recorded using a custom-made proforma. Results: 21.9% of the children were between age 1-2 years, while and 78.1% children were between 3-5 years of Age. Mean age was 4.56±1.357 in both the study groups. 0ver all there were 70.3% male children and 29.7 % were females. In 27.3% of the children duration of the disease was 6 months and 72.7% have more than 6 months. Most of the participated children have weight between 16-20 kg (30.5%), followed by 26.6% have weight more than 30kg, followed by 21.1% have weight between 21-25kg. in 56.2% of the children had a family history of asthma, while 43.8% had no family history of asthma. Group wise distribution of efficacy among 128 children were analyzed as children in Group A (Ipratropium Bromide with Salbutamol) showed 45% decrease number of wheezing episodes and Group B (Salbutamol alone group) showed 51.5% decrease number of wheezing episodes Conclusion: Our research reveals that the addition of ipratropium bromide to salbutamol for the treatment of mild to moderate asthma attacks in children does not improve outcomes over the use of salbutamol alone. Keywords: Efficacy of Ipratropium Bromide with Salbutamol and Salbutamol alone, Recurrent wheezes, Children with asthma